Three-dimensional modelling of oil sand multiphase flow in at face slurry system. (2018) - Zheng, Enzu; Szymanski, Jozef; Hu, Chaoshi
Optimisation of both hydraulic transportation efficiency and production costs are a necessity in the extraction of Athabasca oil sand deposits. There is currently a desire to extend hydraulic transport systems to production faces in oil sand mines using a mobile at face slurry system (AFSS). AFSS consists of multiple pipelines connected with flexible joints, a system which creates slurrified minerals from the mining faces for transportation to processing plants. This paper develops mathematic models governing friction loss associated with AFSS. Modelling of slurry flow is conducted using ANSYS-FLUENT. An arrangement of flexible pipe loops imitating the AFSS was set up to test the accuracy of modelling results. For slurry with a specific gravity of 1.44, solid volume fraction of 0.27, and a velocity of 4 m/s, the simulated pressure gradient associated with an AFSS with a diameter of 0.762 m is 220 Pa/m, compared to 158 Pa/m for the existing stationary system. [Received: March 15, 2016; Accepted: July 27, 2016]